2017
DOI: 10.5430/jbar.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Learning Style Differences between Undergraduates, MBAs, Nonmanagement Workers, and Managers in Japan

Abstract: Using Kolb's experiential learning theory, this study aimed to explore how learning style differed among four cohorts: undergraduate management majors, master's of business administration (MBA) students, nonmanagement workers, and managers. The research context was Japan, with 1080 participants from two universities, one business school, and two different firms focused on sales and production. To compare the four cohors, this study applied a cross-sectional study. Results indicated that managers showed the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although the literature review showed little differences between undergraduate and postgraduate students in terms of leaning style preferences, a number of previous studies which used other instruments to measure students learning style preferences found significant differences between undergraduate and postgraduate students' leaning style preferences (Holtbrügge and Mohr, 2010;Yamazaki and Umemura, 2017).…”
Section: Postgraduate Studentsmentioning
confidence: 89%
“…Although the literature review showed little differences between undergraduate and postgraduate students in terms of leaning style preferences, a number of previous studies which used other instruments to measure students learning style preferences found significant differences between undergraduate and postgraduate students' leaning style preferences (Holtbrügge and Mohr, 2010;Yamazaki and Umemura, 2017).…”
Section: Postgraduate Studentsmentioning
confidence: 89%
“…This suggests that managers require more AC and AE development than non-managers. A recent study about Japanese managers and non-managers indicated that managers had a stronger AE (acting) mode than non-managers (Yamazaki and Umemura, 2017). Based on the three empirical studies in Indonesia, the USA and Japan, results of learning style development in organizations are varied – either more abstract, more active or both.…”
Section: Discussionmentioning
confidence: 99%
“…It is a useful tool to investigate a learning style tendency of a certain group and to compare groups. Kolb’s theory with its learning style instrument has been utilized to help human resource development practitioners and employees recognize various learning approaches (DeSimone et al ., 2002) in terms of different work and career environments (Yamazaki and Umemura, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation